Using Facebook in an EFL Business English Writing Class in a Thai University: Did It Improve Students’ Writing Skills? - Jantima Simpson (Proceedings Education and Language International Conference, 2017)
Facebook, a social media web 2.0 technology, is a popular social network in ASEAN countries currently playing an important role by being integrating and utilised in education. This study investigated whether Facebook influenced writing performances of university students enrolled in an English for Business Course in Thailand. Data results from written pretests and posttests were analysed by applying T-Test, ANOVA and Scheffe´. Results indicated that students with low, medium and high level of wring proficiency significantly improved their writing performances after interacting via Facebook. However, when comparing the three groups, there is a significant difference in the level of improvement between the three groups. Based on this particular aspect, it is evident that further research investigating the factors affecting the high, medium and low achievers would be beneficial as a means of enhancing students writing ability.Keywords: Facebook, writing skills, Business English